Encefalitis equina venezolana. Perfil clínico epidemiológico de la epidemia ocurrida en 1995 - Colina B José Luis; Blanchard Gabriela (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2003)
Abstract: Equine encephalitis in Venezuela has presented itself in epidemic outbreaks in the Venezuelan Guajira since 1936. In 1938 the causal agent was isolated for the first time in a sick horse in Venezuela. The predominant syndrome is that of a self-limiting illness similar to the common cold, and only 4% of the people infected, principally children under 5 years of age, suffer encephalitis. Mortality in children under 5 with encephalitis is 35%. The clinical epidemiological profile of Equine encephalitis in Venezuela between July 15 and October 17 1995, is described and analyzed in relation to 5 municipalities: Maracaibo, Mara, Padilla, Paez, and Miranda in Zulia State. Data obtained from the epidemiological observance and control departments in Zulia is reviewed, including a total of 11,072 cases of clinical, epidemiological diagnosis of Venezuelan equine encephalitis in a population of 574,769 inhabitants in the five municipalities mentioned. The incidence of contagion is 1.92%, and there is no significant difference between sexes. The age group most affected is children under 5 years old, in which half of the mortality occurred (8 cases). This included 2 newborn children whose mothers contracted the disease in the last three months of pregnancy. Resumen: La encefalitis equina venezolana ha venido presentándose en brotes episódicos en la Guajira Venezolana desde aprox. 1936. En 1938 se aisló el agente causal por vez primera de un caballo enfermo en Venezuela. El síndrome predominante es el de una enfermedad autolimitada semejante a la gripe, y apenas 4% de las personas infectadas, principalmente niños menores de 15 años, sufre encefalitis. La mortalidad de niños menores de cinco años con encefalitis es de 35%. Se describe y analiza el perfil clínico epidemiológico de la epidemia de Encefalitis Equina Venezolana en cinco Municipios (Maracaibo, Mara, Insular Padilla, Páez, Miranda) del estado Zulia (Venezuela) ocurrida entre el 15 de Julio y el 17 de Octubre de 1995. Se revisaron los datos obtenidos del departamento de vigilancia epidemiológica del estado Zulia, teniendo un total de 11.072 casos con diagnóstico clínico- epidemiológico de Encefalitis Equina Venezolana, en una población de 574.769 habitantes comprendida por los cincos municipios ya citados, con tasa de ataque de 1,92%, no hay diferencia significativa en el sexo, el grupo etario más afectado son los menores de cinco años ocupando más de la mitad de la mortalidad con 8 casos, incluyéndose en este grupo dos muertes en recién nacidos cuyas madres se enfermaron en el último trimestre del embarazo.